Temporary Flow Diversion in Oncological Embolization Procedures Using Degradable Starch Microspheres - Francesco Giurazza; Pierleone Lucatelli; Fabio Corvino; Renato Argirò; Pietro Roccatagliata; Anna Maria Ierardi; Raffaella Niola (Diagnostics)
Objectives: This study aims to report on the application of degradable starch microspheres to provide flow diversion by means of temporary embolization of healthy tissues in oncological endovascular procedures when tumor feeding vessels are not selectively accessible. Methods: This is a multicenter retrospective analysis of patients undergoing visceral embolization procedures of malignancies. The inclusion criteria were as follows: flow diversion performed by injection of degradable starch microspheres, visceral embolization procedures with unfeasible superselective catheterism of the target, and a malignant pathology. Technical success was defined as complete flow diversion with temporary exclusion of the non-target district from arterial flow, associated with successful embolization of the target. Clinical success was intended as procedural achievement with patient clinical improvement. Results: Sixteen patients were included in this analysis. Peripheral embolization procedures were performed in the coeliac visceral district all in oncologic patients, including 4 transarterial radioembolization work-up procedures in patients with hepatocarcinoma, 10 chemioembolization procedures in patients with hepatocarcinoma (8) or cholangiocarcinoma (2), and 2 palliative transarterial embolizations in patients with gastric cancer. Technical success was obtained in 100% of the cases, while clinical success was reached in 87.5%: in two chemioembolization procedures, despite technical success, the procedural clinical benefits were partial, with an incomplete target lesion response. Minor complications occurred in five patients (31.2%). Conclusions: In this study, temporary flow diversion with degradable starch microspheres during oncological embolization procedures was safe and effective; this approach is suitable to protect healthy surrounding tissues when vessels feeding the target cannot be selected with the microcatheter.